UNIVERSITY THAT OPENS AND TRANSFORMS THE WORLD (CREATIVE AND INNOVATIVE UNIVERSITY) AS A RESPONSE TO THE CHALLENGES OF A NEW ERA - Alexandr P. Gorbunov (Высшее образование в России)
The author analyzes the advantages and shortcomings of the models of “classical”, “research” and “entrepreneurial” university and offers the unique conception of a creative and innovative university that transforms the world. The author argues that this model is an adequate response to the challenges of the new era of economics of knowledge and of creative and innovative competences.